Growth and nutritional status of formula-fed infants aged 2-10 weeks in the Prevention of Mother-to-Child Transmission (PMTCT) Programme at the Dr George Mukhari Hospital, Gauteng, South Africa - MacDougall, Caida (Stellenbosch : Stellenbosch University, 2008)
Thesis (MNutr (Interdisciplinary Health Sciences. Human Nutrition))--Stellenbosch University, 2008.